Topography-modified refraction (TMR): adjustment of treated cylinder amount and axis to the topography versus standard clinical refraction in myopic topography-guided LASIK - Kanellopoulos AJ (Dove Medical Press, 2016)
Anastasios John Kanellopoulos1,2 1LaserVision Clinical and Research Institute, Athens, Greece; 2Department of Ophthalmology, NYU Medical School, New York, NY, USA Purpose: To evaluate the safety, efficacy, and contralateral eye comparison of topography-guided myopic LASIK with two different refraction treatment strategies. Setting: Private clinical ophthalmology practice. Patients and methods: A total of 100 eyes (50 patients) in consecutive cases of myopic topography-guided LASIK procedures with the same refractive platform (FS200 femtosecond and EX500 excimer lasers) were randomized for treatment as follows: one eye with the standard clinical refraction (group A) and the contralateral eye with the topographic astigmatic power and axis (topography-modified treatment refraction; group B). All cases were evaluated pre- and post-operatively for the following parameters: refractive error, best corrected distance visual acuity (CDVA), uncorrected distance visual acuity (UDVA), topography (Placido-disk based) and tomography (Scheimpflug-image based), wavefront analysis, pupillometry, and contrast sensitivity. Follow-up visits were conducted for at least 12 months. Results: Mean refractive error was -5.5 D of myopia and -1.75 D of astigmatism. In group A versus group B, respectively, the average UDVA improved from 20/200 to 20/20 versus 20/16; post-operative CDVA was 20/20 and 20/13.5; 1 line of vision gained was 27.8% and 55.6%; and 2 lines of vision gained was 5.6% and 11.1%. In group A, 27.8% of eyes had over -0.50 diopters of residual refractive astigmatism, in comparison to 11.7% in group B (P<0.01). The residual percentages in both groups were measured with refractive astigmatism of more than –0.5 diopters. Conclusion: Topography-modified refraction (TMR): topographic adjustment of the amount and axis of astigmatism treated, when different from the clinical refraction, may offer superior outcomes in topography-guided myopic LASIK. These findings may change the current clinical paradigm of the optimal subjective refraction utilized in laser vision correction. Keywords: TMR, topography-modified refraction, myopic LASIK, femtosecond laser, FS200, EX500 excimer laser, long-term stability, regression, astigmatism correction, post-LASIK refraction